Bureaucratic Derogatory and Administrative Hierarchy Appraisal with reference to Sub-Continent - Dr. Mughees Ahmed (Journal of Political Studies, 2009)
The study of the bureaucracy as administrative hierarchy designed by British in the political context is the main object of this paper. This chain of command has impersonal behavior with respect to public. It increased powers, by lack of initiative and flexibility by unresponsiveness to human needs and public opinion. Corruption in bureaucracy is increased by tendency to defer decisions to superior and to impede with red-taps. This paper is an attempt to analyze the overall effects of corruption in bureaucracy on the output of political process in the subcontinent. Another main focus of this paper is to analyze the power of non-political elements in politics. Therefore, for the purpose of analysis, we have adapted the historical, analytical and comparative approaches. It is hoped that the outcome of this analysis can provide a solid foundation to extend the spectrum of this research on this issue.